A Self-Learning Module for Grade 7 Students: A Sustainable Enhancement Material for the Least Mastered Competencies in Basic Mathematical Concepts - Mary Grade A. Aledo; Kyla Mae T. Mayo; Emilio James M. Yao; Leroy A. Flores (Future Science / FSH-PH Publications, 2026)
Mathematics is considered one of the most important subjects in the Philippine educational curriculum. However, the majority of students, especially those in junior high school, still struggle with its basic concepts. To address this problem, the researchers developed a self-learning module (SLM) to enhance Grade 7 students’ least mastered competencies in basic mathematical concepts, using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model and a descriptive-developmental research approach. The least mastered competencies of students were analyzed during the needs assessment of researcher-extensionists at a state university in Zambales. The researchers designed and implemented the SLM to help students study independently and understand mathematics better, with features such as various types of activities, practical examples, self-assessment tasks, and bilingual (English and Filipino) explanations, serving as an innovative means of indirect interaction. Results indicated that the SLM effectively addressed learning gaps, as evidenced by improved student performance and favorable evaluation ratings of the module’s design and instructional features. This study implied that the SLM is expected to contribute to the development of effective and accessible learning materials that can sustainably enhance the mathematical proficiency of Grade 7 students, particularly in contexts where language and resource limitations persist.